Current comprehensive understanding of denosumab (the RANKL neutralizing antibody) in the treatment of bone metastasis of malignant tumors, including pharmacological mechanism and clinical trials - Lu, Junjie; Hu, Desheng; Zhang, Yan; Ma, Chen; Shen, Lin; Shuai, Bo (Frontiers in Oncology, 2023)
Denosumab, a fully humanized monoclonal neutralizing antibody, inhibits activation of the RANK/RANKL/OPG signaling pathway through competitive binding with RANKL, thereby inhibiting osteoclast-mediated bone resorption. Denosumab inhibits bone loss; therefore, it is used to treat metabolic bone diseases (including postmenopausal osteoporosis, male osteoporosis, and glucocorticoid-induced osteoporosis), in clinical practice. Since then, multiple effects of denosumab have been discovered. A growing body of evidence suggests that denosumab has a variety of pharmacological activities and broad potential in clinical diseases such as osteoarthritis, bone tumors, and other autoimmune diseases. Currently, Denosumab is emerging as a treatment for patients with malignancy bone metastases, and it also shows direct or indirect anti-tumor effects in preclinical models and clinical applications. However, as an innovative drug, its clinical use for bone metastasis of malignant tumors is still insufficient, and its mechanism of action needs to be further investigated. This review systematically summarizes the pharmacological mechanism of action of denosumab and the current understanding and clinical practice of the use of denosumab for bone metastasis of malignant tumors to help clinicians and researchers deepen their understanding of denosumab.